Rebel - Lu, Marie, 1984- (Lu, Marie, 1984- Legend novel., 2019)
As Day and Eden struggle with who they've become since their time in the Republic, a new danger creeps into the distance between them, and Eden finds himself drawn into Ross City's dark side, where his legendary brother may not be able to save him.